SPACE IN JAPANESE ZEN BUDDHIST ARCHITECTURE - Antariksa Antariksa (Dimensi: Journal of Architecture and Built Environment, 2001)
The beginning in the medieval period the ideas "emptiness" and "nothingness" in Buddhist doctrine influences over the Japanese. Space in Japanese architecture (kukan), as a empty place. This word originally stood for a "hole in the ground", and in on present meaning of a "hole in the universe", or "sky". The ancient Japanese divided space vertically into two parts, sora (sky) and ame or ama (heaven). In the concept of emptiness both of this above it can be said is a part of space. This paper will tries to explain and discusses about the meaning of space in Japanese Zen Buddhist architecture.